The Role of Energy Commodities in Middle East Stock Market Integration - Brahmana, Rayenda; Asmar, Muath (The Berkeley Electronic Press, 2012)
Abstract Given the importance of stock market integration as an indicator of portfolio benefits on the merits of global fund diversification, we test whether the integration of frontier stock market in Middle East ( Jordan, Kuwait, Lebanon, and Oman) can be justified by the movement of energy commodities prices. Using the International capital asset pricing model (ICAPM) in the period January 1997–March 2010, our results indicate that there is a dynamic relationship between energy commodities in the long run. However, the sort linkages of Granger causalities show that only coal and oil Granger-cause market integration. As robustness check, this study investigates the integration of those markets into the European, Australasia, and Far East (EAFE), US, and UK stock markets. Using multivariate regression and after controlling for the size and trading liquidity, we found that there is significant relationship between energy commodities and market integration.